PENINGKATAN KENAMPAKAN SERAT DAN WARNA BEBERAPA JENIS KAYU KURANG DIKENAL UNTUK BAHAN MEBEL - Djoko Purwanto (Kementerian Perindustrian, 2010)
Improved performance of fibers and colors some non commercial timber species for furniture two materials. This study used three types of non commercial wood were Lua (Ficus glomevata Roxb), Tarap (Arthocarpus sp) and Kambang (Goniothalamus sp). Finishing materials used Poly Urethane (PU), Nitro Cellulose (NC), and Antique Finish (AF). Number of spray to finishing material is one time and two times. Results showed that treatment of the finishing process using PU, NC and AF can increase the value of fiber and color performance is quite interesting and attractive, althouht it was decreasing of brightness a decrease in brightness of colors. Spraying of finishing materials one time and two times the power is not obtained by sticking a significant difference. The using of finishing materials to produce type PU adhesive power is better than NC and AF.Keywords: non commercial wood, fibre, colors